Direct observation of water clusters for surface design. (18th May 2020) - Lan, Zhong; Chen, Fangying; Qiang, Weili; Xue, Quan; Ma, Xuehu
Highlights: In-situ IR is applied to online track condensation in the thin layer of cooled wall. Clusters first form in vapor phase, the size evolution relates to distance of wall. Water harvesting mechanism of bionic structure is predicted by cluster distribution. Water-trapping structure has the suitable height to guide functional surface design. Abstract: Engineered surfaces for water collection have been intensively investigated. However, microscopic mechanism of condensation on structural surfaces is rarely explored and it's always a challenge to observe the dynamic behavior of clusters in nanometer size. Here, a measurement is developed to observe cluster along cooling surface. Experimental results show that clusters has been formed before reaching the surface, and condense would be formed by those clusters. Cluster size n gradually increases with closer to the cooling surface, ranging from tens to a few hundreds. Based on the spatial distribution of clusters, the effect of surface microstructures on condensation is analyzed by classical nucleation theory. Surface microstructures can increase the radius of curvature of clusters to exceed the critical size. This key distance is consistent with height of water-trapping villi of some organism. It will help us better understand the scale characteristics of water-trapping structures on some organisms.